Emotional disturbance in planned versus unplanned coloured children and their mothers - Singer, Gerald (Department of Psychology, 2023)
Twenty-nine planned and seventy-six unplanned Coloured children were compared on the Junior Eysenck Personality Inventory, the Purpose In Life test and the Rutter Teachers' Questionnaire for emotional disturbance. Their mothers were also compared on the Eysenck Personality Inventory for neuroticism and the Maryland Parent Attitude Survey. The Purpose In Life test showed the planned children to have significantly more meaning in their lives. No significant differences between planned and unplanned children were obtained on the other two questionnaires. Mothers of unplanned children were found to be significantly more neurotic than mothers of planned children. No differences in maternal attitudes of rejection and protection were found. Differences in the family size and educational attainment of the mothers were significant in the expected direction. It was finally postulated that the greater the adversity of circumstance of the family, the more negative the effects of unplanned status will be on emotional adjustment.